2019
DOI: 10.3390/antiox8070220
|View full text |Cite
|
Sign up to set email alerts
|

Phenol-Rich Feijoa sellowiana (Pineapple Guava) Extracts Protect Human Red Blood Cells from Mercury-Induced Cellular Toxicity

Abstract: Plant polyphenols, with broadly known antioxidant properties, represent very effective agents against environmental oxidative stressors, including mercury. This heavy metal irreversibly binds thiol groups, sequestering endogenous antioxidants, such as glutathione. Increased incidence of food-derived mercury is cause for concern, given the many severe downstream effects, ranging from kidney to cardiovascular diseases. Therefore, the possible beneficial properties of Feijoa sellowiana against mercury toxicity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 60 publications
1
31
0
2
Order By: Relevance
“…Taken together, the findings reported in this paper provide new insight in the Hg-induced alterations in human RBC using a cellular model system on hemoglobin and membrane proteins. Concerning the latter, our work represents the first study revealing alterations of specific membrane proteins, including those of the cytoskeleton, partially responsible for the morphological changes that are reported in our previous studies, consequent to exposure of intact cells in the presence of HgCl 2 [ 23 ]. In particular, the observed structural modification to band 3 could suggest an alteration in the RBC anionic exchange capability that deserves further investigations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Taken together, the findings reported in this paper provide new insight in the Hg-induced alterations in human RBC using a cellular model system on hemoglobin and membrane proteins. Concerning the latter, our work represents the first study revealing alterations of specific membrane proteins, including those of the cytoskeleton, partially responsible for the morphological changes that are reported in our previous studies, consequent to exposure of intact cells in the presence of HgCl 2 [ 23 ]. In particular, the observed structural modification to band 3 could suggest an alteration in the RBC anionic exchange capability that deserves further investigations.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, Wierzbicki et al [ 22 ] reported that workers occupationally exposed to mercuric vapors exhibited a statistically significant increase in blood coagulation along with increased thrombin generation. Interestingly, in vitro exposure of intact red blood cell (RBC) to mercuric chloride (HgCl 2 ) induces morphological changes [ 23 ], which increase their pro-coagulant activity [ 24 ]. RBC are indeed an important target of Hg toxicity because this metal preferentially accumulates in these cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strong antioxidant activity of the feijoa fruit peel was already described on erythrocytes. Tortora et al [44] have recently observed that two polyphenol extracts, obtained from feijoa fruit peel and pulp, are protective against mercury-induced toxicity and oxidative stress, with the first one showing the best activity on intact human red blood cells treated with HgCl 2 [44].…”
Section: Resultsmentioning
confidence: 99%
“…Their employment as additives is broadly distributed in industry field to delay, prevent or eliminate damage caused by oxidation. Recently, some plant extracts have been reported to have good antioxidant and antimicrobial properties due to their polyphenolic and protein compounds (Piscopo et al 2019;Tortora et al 2019;Benabderrahmane et al 2018;Benabderrahmane et al 2019). Due to its complex composition, containing antioxidant dietary fibre, as well as extractable and non-extractable polyphenol content, grape marc extracts have a great potential to display extensive uses in agricultural, pharmaceutical and cosmetic industries among others (Bargiacchi et al 2017;Placha et al 2013;de O Ribeiro et al 2018;Tayengwa and Mapiye 2018).…”
Section: Introductionmentioning
confidence: 99%